A distinção entre conteúdo e objeto na obra Zur Lehre vom Inhalt und Gegenstand der Vorstellungen, de K. Twardowski - Pires, Jesuino Junior (2014)
This work aims to investigate the distinction between content and object of presentation as presented by Kasimir Twardowski in his opuscule Zur Lehre vom Inhalt und Gegenstand der Vorstellungen. Our object of study is the distinction between the content and the object of Twardowski before Brentano and Höfler. This research is characterized as a literature and the procedures are meant for reconstitution, analysis and reflection on the topic. The text is structured in three parts: the first part deals with some points developed by Brentano in his work Psychologie vom Empirischen Stankpunkt, especially with regard to the distinction between psychic and physical phenomena, and, consequently, on his assertion that the whole psychic phenomenon there is something given as immanent object. The second part presents the distinction between content and object, and the particularities of Twardowski before Höfler and Brentano. The main criticism of Twardowski to Brentano is that, like the term presentation , the term presented is also ambiguous and what is meant by immanent object , is in fact the content of representation. For this reason, it is proposed a threefold distinction of psychic phenomenon: act, content and object. This award culminates in the formation of one theory of objects in general, advocated by Twardowski. In the last part of the text some problematic issues are identified regarding the Twardowski s theory mainly on the notion of content and the concept of reality and possibility. Thus, we can infer that the particularities of Twardowski s distinction must be evidenced, firstly by his conception of content as a mediating body between the act and the object of representation; secondly, because this distinction has its linguistic counterpart from the functions name; and finally, through different logical functions performed by the adjective the presented